O ético e poiético no Direito Administrativo - Paola Carvalho Nepomuceno (2015)
It is a job that has in order to expose a study of ethics in Administrative Law that completely loses its essence, if that ethics is not present as primary and guiding element. The aim is to demonstrate that more than the public interest, which really is the foundation of any state action, is Fundamental Rights. It is emphasized that the poietical aspect, always, should be the ethical service, and not the contrary. The aim is to prevent a reversal of these aspects that generates disrespect to citizens. It is valued the ethical purpose as vector the acting state. Fundamental Rights understood as the core of the common good and as limits for the actions of the government will be studied. To build a State that really worry about the realization of justice, the dignity of the human person must be its foundation, as well as respect for Fundamental Rights. The ethical state exists only if there is justice. The Fundamental Rights are much more than principles, they are essence of a Democratic State,